Multicultural Education Theory According to Horace Kallem - Ambo Dalle; St Wardah Hanafie Das (Universitas Muhammadiyah Palu, 2025)
Multicultural Education Theory, as proposed by Horace Kallem, emphasizes the integration of diverse cultural perspectives within educational settings to foster equality and respect among students from various backgrounds. Kallem's theory advocates for a curriculum that not only includes but also respects and values the historical contributions, traditions, and perspectives of different cultural groups. Central to his approach is the idea that education should work as a transformative tool that challenges and rectifies societal inequalities and promotes social justice. Kallem identifies key components of this educational model, which include curriculum reform, teacher training, and inclusive school environments. Through his theoretical framework, Kallem argues that effective multicultural education can reduce prejudice and foster a deeper understanding among students, thus preparing them for a diverse and interconnected world. This abstract synthesizes Kallem's theoretical contributions, which serve as a crucial foundation for ongoing discussions and implementations in educational reform.